Diagnostic Accuracy of SWAN in the Diagnosis of Low-Flow Brain Vascular Malformations in Childhood - Akyel, Nazlı Gülsüm; Alımlı, Ayşe Gül; Sivri, Mesut; Akmaz Ünlü, Havva; Tiftik, Mehmet (Journal of Pediatric Neurology, 2021)
Purpose The main objective of this study is to demonstrate the diagnostic accuracy of susceptibility-weighted angiography (SWAN) in the diagnosis of slow-flow cerebral vascular malformations, especially developmental venous anomaly (DVA). We also aimed to determine the prevalence of DVAs identified by SWAN at 1.5 T.Methods We retrospectively evaluated 1,760 axial SWAN images for the diagnosis of low-flow vascular anomaly. Among them were 305 patients who underwent contrast-enhanced examination due to different indications. Postcontrast images were analyzed by different radiologists who were blinded to patients. The presence of DVA and other features such as location, length, depth, and direction of drainage vein was evaluated.Results Twenty-six patients with DVA had both SWAN and postcontrast images. There were four false-negative patients with SWAN. The sensitivity of the SWAN sequence was 84.6%. In addition, totally 77 DVA (4.36%), 2 capillary telangiectasia (0.11%), and 2 cavernous malformations (0.11%) were detected in 1,760 patients.Conclusion SWAN is an effective method for the diagnosis of developmental venous anomalies and other low-flow cerebral vascular malformations. Especially in the pediatric age, susceptibility-weighted imaging sequences are useful to limit contrast use.
Keywords: developmental venous anomaly; cavernous angiomas; capillary telangiectasia; susceptibility-weighted angiography; susceptibility-weighted imaging; magnetic resonance imaging